State in 18 O by using Core – Polarization effects - Salman , Emad (University of Thi-Qar Journal of Science, 2008)
Coulomb form factors for E0 transition in 18O are discussed taking into account core-polarization effects. These effects are taken intoaccount through the collective model of Tassie and also through a microscopic perturbation theory including excitations up to 2p1f shell.Space wave model functions defined for the orbits 1 and 2125O nucleus has been thesubject of extensive theoretical and experimental studies, which receivedmuch attention in last decade [Alex Brown et.al.2005]. The 18O systemcontains two neutrons in addition to the16O core distributed in the sd – shell. d1 are obtained from the diagonalization of the interaction Hamilonian of Wildenthal. The calculations include the 02state with excitation energies3.6337MeV. The core – polarization effects which incorporate the ollective model of Tassei describe the data very well for this state.